2021
DOI: 10.5829/ije.2021.34.06c.05
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Load Balancing and Dynamic Placement of Virtual Machines in Cloud Computing using Particle Swarm Optimization Algorithm

Abstract: Nowadays, maximizing profits, decreasing operating cost and scheduling tasks are the most important issues of cloud computing with its growing usage. In this regard, one of the challenges in cloud computing is to provide an efficient method to deploy virtual machines on physical machines with the aim of optimizing energy consumption, fair load distribution and task scheduling. The purpose of present study is to provide a method for improving task scheduling through an improved particle swarm optimization algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Particle swarm algorithm is an intelligence algorithm to simulate the bird flock foraging. Each particle is characterized as a possible solution vector [21][22][23][24]. The quality of particles is judged by the value of fitness function.…”
Section: Basic Principles Of Improved Particle Swarm Algorithmmentioning
confidence: 99%
“…Particle swarm algorithm is an intelligence algorithm to simulate the bird flock foraging. Each particle is characterized as a possible solution vector [21][22][23][24]. The quality of particles is judged by the value of fitness function.…”
Section: Basic Principles Of Improved Particle Swarm Algorithmmentioning
confidence: 99%
“…The results showed that this algorithm performs well in case of increasing the number of tasks. Yousefipour et al [13] proposed a method for task scheduling improvement of cloud computing through an improved particle swarm optimization algorithm. In this method, selection of a proper objective function has led to balanced workload of virtual machines, decreased time of all tasks as well as maximum utilization of all resources and increased productivity in addition to dynamic placement of virtual machine on physical machine.…”
Section: Related Workmentioning
confidence: 99%
“…An improved Particle Swarm Optimization algorithm was designed [11] for the balanced workload of virtual machines. However, the higher efficiency of workload balancing was a challenging task.…”
Section: Introductionmentioning
confidence: 99%